June - Copeland, Lori (Carol Stream, Ill. : Tyndale House, 2007)
June leaves her home in Michigan to become a mail-order bride to a young Washington State pastor and finds herself faced with difficult choices that challenge her faith and her heart.
aOriginally published: Wheaton, Ill. : Tyndale House, c1999.